2011
DOI: 10.5271/sjweh.3148
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of research case definitions for carpal tunnel syndrome

Abstract: Objective The aim of our study was to assess agreement between different case definitions of carpal tunnel syndrome (CTS) for epidemiological studies. Methods We performed a literature search for papers suggesting case definitions for use in epidemiological studies of CTS. Using data elements based on symptom questionnaires, hand diagrams, physical examinations and nerve conduction studies collected from 1107 newly-hired workers, each subject in the study was classified according to each of the case definiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 42 publications
0
26
1
Order By: Relevance
“…Clinical diagnosis of CTS is complex and a variety of research and/or surveillance case definitions for CTS and work-related musculoskeletal disorders in general have been proposed and evaluated, many of which are based on combinations of reported symptoms, physical exam findings, and/or electrodiagnostic studies [e.g., Silverstein et al, 1997;Rempel et al, 1998;Descatha et al, 2011]. Unfortunately, due to the nature of this study (i.e., relying on data collected from a few questions that were part of a broad health questionnaire), we were only able to use a very crude case definition for CTS: self-report of a clinician diagnosis of CTS.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Clinical diagnosis of CTS is complex and a variety of research and/or surveillance case definitions for CTS and work-related musculoskeletal disorders in general have been proposed and evaluated, many of which are based on combinations of reported symptoms, physical exam findings, and/or electrodiagnostic studies [e.g., Silverstein et al, 1997;Rempel et al, 1998;Descatha et al, 2011]. Unfortunately, due to the nature of this study (i.e., relying on data collected from a few questions that were part of a broad health questionnaire), we were only able to use a very crude case definition for CTS: self-report of a clinician diagnosis of CTS.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…This finding is in line with the results of a recent systematic review that highlighted that complex case definitions (eg, based on examinations) for upper-limb disorders (including CTS) yield similar associations with occupational determinants to those obtained using simple case definitions based on Bonfiglioni et al symptoms (35). Moreover, findings from a review on the case definitions for CTS in epidemiological studies suggested the possibility of comparing the results obtained in studies adopting various case definitions of CTS, based on different combinations of symptoms, clinical examination, and/or NCS (36).…”
Section: Noncasementioning
confidence: 99%
“…Descatha et al demonstrated that the prevalence of carpal tunnel syndrome varied according to the case definition employed, leading to the misclassification of 1% to 10% cases. Despite this finding, the agreement between different case definitions was found to be acceptable and allowed for the comparison of prevalence rates across different studies 31 . Our difficulty with the definitive identification of cubital tunnel syndrome in the setting of possible carpal tunnel syndrome resulted in considerable uncertainty and variability in observed cubital tunnel syndrome frequency.…”
mentioning
confidence: 97%
“…In this study, the combination of a hand diagram and the BCTQ was chosen to create a diagnostic test with the ability to identify cubital tunnel syndrome and carpal tunnel syndrome-related symptoms (hand diagram) and to identify patients with a symptom severity consistent with carpal tunnel syndrome or cubital tunnel syndrome. We also chose this definition on the basis of evidence that these tests both demonstrate strong correlation with electrophysiologic diagnosis 21,31 . Typically, screening for cubital tunnel syndrome relies on multiple methods (patient-reported history of symptoms, clinical examination, electrodiagnostic testing, ultrasonographic examination) that all have diagnostic limitations 1,32,33 .…”
mentioning
confidence: 99%